Stem Cells - From Drug to Drug Discovery - Abdalla, Elmuataz Elmansi; Afroze, Salman; Ali, Anwar; Alsharida, Mansour; Gopu, Sriram; Guo, Changfa; Haider, Khawaja Husnain; Khan, Irfan; Latief, Noreen; Lei, Ye; Mehmood, Azra; Naeem, Nadia; et al. (De Gruyter, 2017)
Stem cell based therapy is a 21st century approach of therapeutic intervention which epitomizes a shift from conventional symptomatic treatment strategy to addressing the root cause of the disease process. This is especially a hope for the patients suffering from diseases such as Alzheimer, diabetes, myocardial infarction and other diseases which have always been considered as incurable. Moreover, stem cells provide excellent in vitro disease models for drug development. This book is a compilation of the bench experience of experts from various research labs involved in the cutting edge area of research, describing the use of stem cells both as part of the combinatorial therapeutic intervention approach and as tools (disease model) during drug development.